The relevance of sports financing - Patrícia Becsky-Nagy; Tamás Dékán; Réka Szőke; Zoltán Bács (Apstract: Applied Studies in Agribusiness and Commerce, 2015)
According to estimations sports exploit approximately two percent of world GDP. In addition sports represent an important function in culture, socialization and also in education, act an outstanding role in economy, as well, though academic researchers cannot find positive relationship between sports financing and economic growth. Sports were originally civil actions, with non-profit nature, where they did not aspire to reach high returns, but fulfilment of sport itself. However returns can be realized and reinvested in sports. This paper tries to collect the different aspects of sports financing in order to highlight its relevance.